Changes in lung function and dyspnea perception in Colombian Covid-19 patients after a 12-week pulmonary rehabilitation program. - Carlos D Páez-Mora; Diana Carolina Zona; Teddy Angarita-Sierra; Matilde E Rojas-Paredes; Daniela Cano-Trejos (PLoS ONE)
Background Although moderate and severe Covid-19 patients have shown obstructive and restrictive disorders in pulmonary function after recovery from the disease, studies evaluating the effectiveness of rehabilitation programs that seek to improve lung function are scarce. Aim Herein, we evaluate changes in lung function and perceived dyspnea in Covid-19 patients after undergoing 12 weeks of a pulmonary rehabilitation (PR) program. Design Retrospective observational study. Setting Cesar, Colombia Neumocesar Pneumological Center. Population 100 outpatients with a history of Covid-19. Methods Respiratory function using spirometry parameters, as well as perceived dyspnea, measured by the modified Medical Research Council (mMRC) dyspnea scale, was evaluated in 100 patients with a history of Covid-19. We used univariate and multivariate statistical approaches to assess changes in lung function and perceived dyspnea before and after a PR program to determine whether gender, age, height, weight, comorbidities, and oxygen delivery system affects the recovery of lung function and perceived dyspnea. Results It was found that PR treatment has positive effects on respiratory pathologies caused by SARS-CoV-2 infection regardless of patient gender (S = 0,029), indicating that rehabilitation provided benefits regardless of the physical characteristics of the patients. Both univariate and multivariate statistical analyses indicated that FVC (P = 0,0001), FEV1(P = 0,0001), and mMRC (P = 0,0001) are robust diagnostic indicators of lung function recovery and perceived dyspnea. Both invasive and non-invasive positive pressure ventilatory support had deleterious effects on lung function prolongating patient recovery (P = 0,0001). Conclusions Rehabilitation programs can benefit patients facing respiratory pathologies caused by SARS-CoV-2 infection. Additional research on the long-term effects of the sequelae of Covid-19 is needed. Clinical rehabilitation impact PR programs have positive effects on patients facing respiratory pathologies caused by SARS-CoV-2 infection.